Suboptimal guidance law against maneuvering target with time and angle constraints - Xie, Jiliang; Ma, Kemao (Aerospace science and technology, 2024)
The impact time and angle constrained terminal guidance laws against a maneuvering target are usually designed under the assumption that the magnitude of the missile's velocity can be controlled, rather than a missile with uncontrollable speed because it is difficult to adjust the time-to-go due to the maneuver of the target. The main objective of this work is to propose a new guidance law to access the ability of hitting a maneuvering target at the desired impact time and terminal angle under the assumption that the magnitude of the missile's velocity is uncontrollable. In the design, the linearized relative kinematic equations are constructed, then used in the design of optimal guidance law with terminal angle constraint. The analytical formula of the time-to-go estimation is obtained based on the optimal guidance law, which is used to design a bias term to meet the impact time constraint. Numerical simulations are conducted for different engagement scenarios to verify effectiveness of the design.